Sulfation of Glycosaminoglycans Modulates the Cell Cycle of Embryonic Mouse Spinal Cord Neural Stem Cells - Schaberg, Elena; Theocharidis, Ursula; May, Marcus; Lessmann, Katrin; Schroeder, Timm; Faissner, Andreas (Frontiers in Cell and Developmental Biology, 2021)
In the developing spinal cord neural stem and progenitor cells (NSPCs) secrete and are surrounded by extracellular matrix (ECM) molecules that influence their lineage decisions. The chondroitin sulfate proteoglycan (CSPG) DSD-1-PG is an isoform of receptor protein tyrosine phosphatase-beta/zeta (RPTPb/z), a trans-membrane receptor expressed by NSPCs. The chondroitin sulfate glycosaminoglycan chains are sulfated at distinct positions by sulfotransferases, thereby generating the distinct DSD-1-epitope that is recognized by the monoclonal antibody (mAb) 473HD. We detected the epitope, the critical enzymes and RPTPb/z in the developing spinal cord. To obtain insight into potential biological functions, we exposed spinal cord NSPCs to sodium chlorate. The reagent suppresses the sulfation of glycosaminoglycans, thereby erasing any sulfation code expressed by the glycosaminoglycan polymers. When NSPCs were treated with chlorate and cultivated in the presence of FGF2, their proliferation rate was clearly reduced, while NSPCs exposed to EGF were less affected. Time-lapse video microscopy and subsequent single-cell tracking revealed that pedigrees of NSPCs cultivated with FGF2 were strongly disrupted when sulfation was suppressed. Furthermore, the NSPCs displayed a protracted cell cycle length. We conclude that the inhibition of sulfation with sodium chlorate interferes with the FGF2-dependent cell cycle progression in spinal cord NSPCs.